The design of content & language integrated learning (CLIL) course for the interwoven development of content, communication, cognition & culture - Amado Valdivia, Ana Paola (2012)
This investigation explores the principles of CLIL for the design of a content-based course called Art History & Appreciation. These principles constitute the beliefs that direct the decisions about the course objectives, content, method and evaluation. Thus, an integrated model of curriculum is expected to be developed. The products of this model, that is, the syllabus, lesson planning, materials and tests are also immersed in the context of CLIL and other related theories, like Task-Based Learning, which permits its implementation in the classroom, and Communicative Language Ability, which sets the components for the evaluation of its effectiveness.